The Law Enforcement Against Traffic Violations By Minor Children - Wahyu Handono; Siti Rodhiyah Dwi Istinah (Law Development Journal, 2021)
The purpose of this research is to identify and analyze law enforcement against traffic violations by minors at the Semarang Police Station and to identify and analyze the obstacles to law enforcement against traffic violations by minors at the Semarang Police Station. This study uses a sociological juridical approach, which in this case relates to law enforcement against traffic violations by minors at the Semarang Police Station, with descriptive analytical research specifications. The data used are primary and secondary data which will be analyzed qualitatively. The research problem was analyzed using the theory of justice and the theory of the operation of law. The results of the study conclude that law enforcement against underage traffic violations is through preventive and repressive efforts. Conceptually, the handling of criminal acts in Indonesia is integrated, both within the internal scope of the National Police and within the scope that involves other components outside the National Police. In handling traffic violations by minors, problems arise because they are caused by a lack of legal awareness in the community, lack of traffic discipline, lack of legal socialization, inconsistent law enforcement and selective slashing, aspects of legal culture, and sanctions that are too light.